Proceedings of the 22nd International Scientific Conference on Applications of Mathematics and Statistics in Economics (AMSE 20 2019
DOI: 10.2991/amse-19.2019.14
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of socio-economic development of selected European countries with the use of a modified HDI

Abstract: The aim of the paper is to analyse the socioeconomic development of selected European countries represented by various social policies, and to verify the hypothesis of different speeds of development within the groups into which these countries divide. The following groups are considered in the analysis: Post-Communist countries (the Visegrad Group countries, Lithuania, Latvia, Slovenia and Estonia); Scandinavian countries (Denmark, Finland and Sweden); so-called welfare states and "Old Europe" countries (Germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The human development index (HDI) is designed to reflect the level of income, education, and health in the general population. Biernacki and [ 3 ] provide evidence to confirm the observation that the dynamics of quality of life development in the years 2006–2015, measured by a modified HDI index for the EU area, was significantly more pronounced in the segment of developing economies (compared to that in mature and decidedly more affluent economies).…”
Section: Introductionmentioning
confidence: 76%
“…The human development index (HDI) is designed to reflect the level of income, education, and health in the general population. Biernacki and [ 3 ] provide evidence to confirm the observation that the dynamics of quality of life development in the years 2006–2015, measured by a modified HDI index for the EU area, was significantly more pronounced in the segment of developing economies (compared to that in mature and decidedly more affluent economies).…”
Section: Introductionmentioning
confidence: 76%
“…In line with orthodox theory, a positive relationship was found between the labour force's level of educational attainment and competitiveness. While in the European Economic Area (EEA17), tertiary education is the only significant education-based determinant of the export market share, in EECs both the shares of the workforce with secondary and tertiary education are significant with the former having a greater impact (Biernacki & Guzek, 2019;Fomina, Sizikova, Shimanovskaya, Kozlovskaya, & Karpunina, 2019). This conclusion regarding the Eastern European countries is not consistent with our finding that in Kazakhstan no relationship is found between the economic growth and the expenditures on secondary and higher professional education.…”
Section: Discussionmentioning
confidence: 99%
“…To analyse the socio-economic development of 20 European countries with varied social policies, Biernacki and Guzek (2019) used a modified Human Development Index (HDI) based on several sources (including EHCI (Euro Health Consumer Index) and PISA (Program for International Student Assessment), and GDP for 2006-2015. The results of the study showed that the dynamics of HDI of countries corresponds to the dynamics of GDP: the more rapid is the dynamics of HDI growth of a country, the more rapid is the dynamics of GDP growth (Biernacki & Guzek, 2019). The research of Roopchund (2017) also found a direct link and correlation between the HDI and the economic growth of a country.…”
Section: Introductionmentioning
confidence: 99%
“…Studies to analyse the effectiveness of the implementation of SEP as a whole or of its individual indicators are regularly conducted both in Europe (Biernacki and Guzek, 2019;Cordero, Karkazis, and Thanassoulis, 1998;Kulakov and Lysunets 2017;Pedraja-Chaparro, Pisaflores, and Polo, 2017;Stanković, Marjanović, and Stojković, 2021;Večerník, 2009) as well as worldwide (Zhang, Hara, Yabar, Yamaguchi, Uwasu, and Morioka, 2009). Similar studies conducted in Latvia are usually related to the analysis of a limited range of key indicators of social policy (Bikava and Skride, 2018;Corazza, Kļaviņa, Lepiksone, and Nuti, 2019;Shtals, Tsaurkubule, Konstante, and Alksnis, 2020).…”
Section: Efficiency and Effectiveness Of Sepmentioning
confidence: 99%